2012
DOI: 10.1051/0004-6361/201117664
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of CH+and SH+absorption lines observed towards distant star-forming regions

Abstract: Aims. The HIFI instrument onboard Herschel has allowed high spectral resolution and sensitive observations of ground-state transitions of three molecular ions: the methylidyne cation CH + , its isotopologue 13 CH + , and sulfanylium SH + . Because of their unique chemical properties, a comparative analysis of these cations provides essential clues to the link between the chemistry and dynamics of the diffuse interstellar medium. Methods. The CH + , 13 CH + , and SH + lines are observed in absorption towards th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
189
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(208 citation statements)
references
References 88 publications
15
189
4
Order By: Relevance
“…For low-density diffuse interstellar clouds, C-shocks (Pineau des Forêts et al 1986) and turbulent dissipation (Godard et al 2009) have been proposed and confirmed by Falgarone et al (2010a,b) and Godard et al (2012). Alternatively, in denser regions with strong far-ultraviolet (FUV) radiation fields, the internal energy available in the vibrationally excited H 2 molecules A&A 550, A96 (2013) has been proposed to help overcome the large activation barrier (Sternberg & Dalgarno 1995;Agundez et al 2010).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…For low-density diffuse interstellar clouds, C-shocks (Pineau des Forêts et al 1986) and turbulent dissipation (Godard et al 2009) have been proposed and confirmed by Falgarone et al (2010a,b) and Godard et al (2012). Alternatively, in denser regions with strong far-ultraviolet (FUV) radiation fields, the internal energy available in the vibrationally excited H 2 molecules A&A 550, A96 (2013) has been proposed to help overcome the large activation barrier (Sternberg & Dalgarno 1995;Agundez et al 2010).…”
Section: Introductionmentioning
confidence: 86%
“…Menten et al 2011) and properties of turbulent dissipation regions (e.g. Godard et al 2012), in clouds exposed to high UV irradiation these abundances are sensitive to the abundance ratios of H, H 2 , and electrons as a function of depth into the cloud, which are determined by the radiation field strength of the irradiation source.…”
Section: The Destruction Of Ch + and Sh +mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, their reaction products will be formed at detectable abundance if the corresponding reaction endothermicity is overcome by turbulent dissipation, shocks, or shears. Submillimeter absorptions from both the neutral SH, that is, the mercapto radical, and the sulfanylium (SH + ) have been observed in foreground diffuse molecular clouds toward star-forming regions (Menten et al 2011;Godard et al 2012;Neufeld et al 2012Neufeld et al , 2015. Consequently, the analysis of sulfur hydrides provides unique physical and chemical constraints on models that are applied to the interstellar medium.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the analysis of sulfur hydrides provides unique physical and chemical constraints on models that are applied to the interstellar medium. In particular, SH + has been suggested as an important probe of turbulence in the diffuse ISM (Godard et al 2012(Godard et al , 2014.…”
Section: Introductionmentioning
confidence: 99%